Role of Nurses in the Prevention and Early Detection of Oral Cavity and Pharynx Cancers - Patricia Da Rosa; Lori Koenecke; Laura Gudgeon; Whitney Keller; Wei Gu (Rural Nurse Organization; Binghamton University, 2021)
Purpose: The incidence of oral cavity and pharynx cancer is rising in the United States and South Dakota (SD) (2009-2018). In 2018, it was estimated that 396,937 of Americans were living with oral cavity and pharynx cancer. The 5-year relative survival rate for oral cancer is 66.2%, which is less than the survival rates for breast, colorectum, and prostate cancers. Tobacco and alcohol use and human papillomavirus (HPV16) exposure are some of the risk factors for oral cancer. Overall rural populations have higher cancer mortality than no rural population due to higher poverty, lower access to health services, and cigarette use. The purpose of this study is to investigate the prevalence of the oral cancer risk factors (e.g., cigarette smoking), HPV vaccination rates, and to identify the spatial distribution of social and environmental factors (e.g., social vulnerability, dental care access) in SD. Finally, this article discusses how nurses can contribute to oral cancer prevention and early detection. Methods: This descriptive study used data from multiple data sources (e.g., SD Department of Health, HRSA, County Health Rankings). Maps were created using ArcGIS.  Findings: From the 66 SD counties, nearly 17% presented high-level shortage scores and were also highly socially vulnerable. HPV vaccination among youth was higher than the national average. Studies showed that improving nurse's knowledge by training on oral cancer is needed and this may increase nurses' practice in oral cancer prevention and control.  Conclusions: Primary care professionals like nurse practitioners can assist in early detection of oral cancer and promote awareness of signs and main risk factors in rural areas. As part of the total patient care, nurses hold a vital role in prevention and early detection of oral cancer. These efforts with referral to oral cancer screening are vital for decreasing oral cancers morbidity and mortality rates primarily.  Keywords: Rural health, Nurses, oral cancer, dentalcare access, Geographic Information Systems DOI:  https://doi.org/10.14574/ojrnhc.v21i2.692